Endettement du Cameroun: Problèmes et solutions - Samuel Fambon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Ce papier étudie les problèmes d'endettement extérieur du Cameroun en analysant son évolution globale (structure, service de la dette, conditions des emprunts, etc.). Cette analyse est complétée par l'examen de la dette intérieure compte tenu de son poids dans la dette totale du pays. Après avoir retracé les origines de la crise d'endettement, le papier aborde les différentes solutions appliquées à la dette extérieure camerounaise, les perspectives d'avenir de la dette, les politiques de minimisation des crises d'endettement et les stratégies susceptibles d'alléger considérablement la dette intérieure publique du pays. – Dette ; Allégement de la dette ; Initiative PPTE ; Soutenabilité de la dette ; Cameroun – – This paper evaluates Cameroon's foreign debt situation by analysing its evolution (structure, debt service payment, debt ratio, borrowing conditions, etc.). The analysis is extended by examining the internal debt situation, taking into account its weight in the global endebtness of the county. After charting out the origin of the debt crisis, the paper outlines the different solutions that have been meted to ease the external debt situation, notably: the future prospects of the debt situation, policies to attenuate the debt crisis, as well as strategies capable of considerably reducing internal public debt in the country. – debt ; debt relief ; HIPC ; debt sustainability ; Cameroon
Keywords: F34; O11; O55; 330; Auslandsverschuldung; Schuldenerlass; Kamerun